Culture-based potential for the development of cities in Poland - Orankiewicz, Agnieszka (Potencjał kulturowy dla rozwoju miast w Polsce, 2019)
The discussion in this article concerns the identification of the culture-based development potential of cities, and the aim of the study, is to classify urban communes (boroughs) in Poland in terms of their culture-based development potential. A multidimensional comparative analysis was used to build a measurement tool and to create rankings of cities. The proposed measure includes five groups of diagnostic variables referring to the cultural infrastructure, cultural events, creative sector, tourist base and public finances. Data from 306 urban communes in Poland from 2013-2016 were collected for the study. The article presents selected research results, such as rankings of cities with the highest City Culture Potential index. This is due to the visibly differentiated strategies for building a competitive advantage, which result in different intensities and the importance of factors assumed as explanatory variables in measuring the potential of culture
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 4, s. 108-121
Keywords: city development; culture; measures; rozwój miast; kultura; pomiar